THE DEVELOPMENT OF BILINGUAL TEXTBOOK INTEGRATED ISLAMIC SPIRITUAL VALUE ON INVERTEBRATE MATERIAL FOR SENIOR HIGH SCHOOL GRADE 10th - Rizqa Damas Sa’diyah; Reni Ambarwati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2018)
Nowadays, emerging modern schools based on Islamic boarding schools that promote the spiritual competence and global development to emphasize the mastery of science, religious, and international language. However, not all local students are ready to use the international language in learning activity, so it is necessary to develop a bilingual textbook consisting of English and Indonesia Language. This research aimed to develop bilingual textbook integrated with Islamic religious value on invertebrate material, which fulfills validity and practicality. This development research was referred to Fenrich Instructional Development Cycle Model contains analysis, planning, design, development, and implementation phase, which each cycle through the evaluation and revision phase. The development of textbook was conducted in the Biology Department FMIPA UNESA and the limited trial was conducted on 15 students of SMA Progresif Bumi Shalawat grade 10th. The validity of the textbook was assessed by a biology education expert, an animal taxonomy expert, and an Islamic religious expert. The practicality of the textbook was assessed based on the Fry Graph readability test and the students’ responses. Data were analyzed descriptive-quantitatively. The validity of the textbooks acquired very valid category, hence the textbook was appropriate to use in the learning activity. The Fry Readability Graph test of the textbook was at 10 level and the student’s positive responses to the textbooks get an average of 94% very good category, hence the textbook was practical to use in the learning activity. Thus the bilingual textbook integrated Islamic religious value on the invertebrate material was declared valid and practically used in biology learning activity. Keywords: Bilingual, Invertebrate, Islamic Spiritual Value, Textbook.